Cross-level considerations for explaining selection pressures and the maintenance of genetic variation in condition-dependent male morphs - Smallegange, Isabel M; Rhebergen, Flor T; Stewart, Kathryn A (Current opinion in insect science, 2019)
•Condition-dependent expression of alternative male morphs occurs in many arthropods.•Morph expression depends on future performance or is caused by energy budgets.•Somatic state-dependence of morph expression is untested, but likely crucial.•Weak or balancing selection maintains genetic variation in male morph expression. Condition-dependent expression of alternative male morphologies (AMMs) exists in many arthropods. Understanding their coexistence requires answering (at least) two questions: (i) what are the ecological selection pressures that maintain condition-dependent plasticity of AMM expression, and (ii) what maintains the associated genetic variation? Focusing on acarid mites, we show that the questions should not be conflated. We argue how, instead, answers should be sought by testing phenotype-level (question 1) or genotype-level (question 2) hypotheses. We illustrate that energy allocation restrictions and physiological trade-offs are likely to play a crucial role in AMM expression in acarid mites. We thus conclude that these aspects require specific attention in identifying selection pressures maintaining condition-dependent plasticity, and evolutionary processes that maintain genetic variation in condition-dependent phenotypic plasticity.